The Paradox of Poverty Reduction and the Reality of Sustainable Structural Poverty - Fitriani, Masfiah Diana; Nadofah, Nadofah (Proceeding International Conference on Religion, Science and Education, 2025)
The purpose of this research is to reveal the reality that the Indonesian poverty rate is still quite high, although there are many implementations of poverty policies and poverty reduction programs. Structural poverty is one of the poverty types determining the sustainability of poverty rates. Some people mention structural poverty as heirs. Structural poverty has many unexpected conditions and reasons why “the poor stay poor, and the rich become richer”. Sometimes, poverty is created, not just appears. This research uses a qualitative method approach. The analysis is based on primary and secondary data from the field notes, observation, and literature review. The result found that many poverty policies and poverty reduction programs along the way are just formalities. No programs or policies aim to reduce the poverty structure or address its root causes. The currently poor will probably live poor in the future because of the lack of accessibility to feasible education, health facilities, feasible wages, and career opportunities. Even, though there is employee exploitation, capital accessibility barriers, academic clustering, ambiguous regulation of welfare rights, the burden of tax rate, and other inequality of chance, supposed zero poverty is never reached. Therefore, even though poverty alleviation policies have been implemented for a long time, the rate of poverty reduction has not occurred significantly. Structural poverty is one type of poverty that requires collaborative governance in its resolution, because in efforts to eradicate poverty, especially structural poverty, many policies are needed that must be integrated into various lines of community life.